A power-sharing multiple-beam mobile satellite in Ka band. - Egami, S. (IEEE Journal on selected areas in communications)
This paper presents a new power-sharing multiple-beam mobile satellite system concept in the Ka band. A wide allocated bandwidth and a large amount of frequency reuse based on hundreds to thousands of small spot beams will allow us to draw a drastically new mobile satellite systems concept in the Ka band. At first, requirements for beam size on the surface of the Earth for various signal transmissions are considered. Based on these requirements, Ka band geostationary systems with 3.5 and 10 m satellite antennas are shown. If the number of beams is hundreds to thousands, it is not appropriate to assume a fixed power transmitter for each beam because the traffic in each beam is not uniform or static. In order to cope with this multiple-beam-varying traffic problem, this paper proposes a new type offset reflector antenna fed through an equal phase-shift active array. The proposed active array consists of hundreds to thousands of equal phase-shift elements. Features and simulated performances of the proposed transmitting antenna are presented. Preliminary experimental results from a 2.1 m reflector fed through 332 hollow elements are also shown. Since each beam commonly utilizes all active array elements, power sharing among beams is possible, allowing traffic variation among beams without loss of power efficiency